Efektivitas Batas Usia Perkawinan Terhadap Budaya Perkawinan Anak Di Kabupaten Probolinggo Perspektif Teori Efektivitas Hukum - Ubaidila; Putri Meilinda , Fauziyah (Maqasid: Jurnal Studi Hukum Islam, 2024)
This research analyzes the effectiveness of implementing marriage age limits on the culture of child marriage in Probolinggo Regency based on the perspective of legal effectiveness theory. The main aim of this research is to assess the extent to which the legal provisions in Law no. 16 of 2019 concerning increasing the minimum age limit for marriage to 19 years has succeeded in reducing the number of child marriages. This research method uses a qualitative approach, with data collection through interviews, observation and document study. The research results show that this law is not yet effective, as indicated by the high number of requests for marriage dispensation in Probolinggo Regency. Factors that influence this ineffectiveness include legal substance that still provides opportunities for dispensation, lack of public awareness of marriage age regulations, as well as cultural influences that view early marriage as an economic and social solution. This study recommends increasing legal education in the community and stricter supervision to reduce the prevalence of child marriage